Pengamatan Pergerakan Limbah Minyak Goreng Berdasarkan Nilai Resistivitasnya dengan Menggunakan Metode Crosshole Dipole-Dipole - Supriyadi Supriyadi; Nurul Priyantari; Agus Supriyanto; Najibur Rohim (Lambung Mangkurat University Press, 2018)
The area around of Jember University has potential as a trading area because the majority of its citizens are immigrants. This potential is utilized by street food vendors located around the University of Jember. Most street vendors dispose of waste i.e used cooking oil directly around trading locations. One methode to determine waste seepage in the soil is to use the geoelectric method with crosshole dipole-dipole configuration. This research is a laboratory scale research. The sample of soil and waste of used cooking oil were taken from the location of street vendors around Jember University. Based on the research results, the soil resistivity value before being given the waste is 2.78 Ωm to 7.52 Ωm. While the value of soil resistivity after given the waste of used cooking oil ranged from 0.01 Ωm to 5.15 Ωm. Observations from the first day to the seventh day indicate that the movement of waste used cooking oil occurs vertically due to gravity and in all directions due to capillarity.